A Comparative Study Between Some of the Local Iraqi Method for Curing Chicken Meat and Typical Methods and Their Effect on Chemical Composition, Sensory Evaluation of Fresh and Storage Meat - Al-Hajo, Nadia N.A. (International Journal of Poultry Science, 2008)
This research work was carried out to study some of local Iraqi method of chicken meat curing in comparison with the typical method and its effect on chemical composition and sensory evaluation of fresh and storage meat compared with uncured meat (T1). Citric acid and salt (T2) were used in curing meat of the local Iraqi method (T2). Vineger and garlic (T3), While, brine solution was used with the typical method (T4). Curing was conducted under 4oC for 24 h. The samples storage for 0, 15 and 30 day under-18oC. The data revealed a significant increase (p<0.05) in moisture of the cured treatment compared with the control. T2 have a higher percentage of moisture. The data indicated no significant differences in moisture content of all treatments as the period of storage increased. The data further, reveal the percentage of protein was decreased significantly (p < 0.05) in cured treatment compared with the control. No significant differences between treatments as the period of storage increased. Fat content of cured treatment compared with the control did not differ significantly for all periods of storage. While ash content increased significantly (p<0.05) during curing, T4 have a high percent, there were no significant differences between treatment during the storage period increased compared with all treatment. No significant differences in pH value, T3 have a low percent (p < 0.05) in pH. There were significant differences (p < 0.05) between T1, T3 and T2, T4 were notice with regard to the percentage of cooking loss. The organoleptic assessment for color score was notice to decreased significantly (p<0.05) for treatment T1, T2, T3 while increased significantly (p<0.05) for T4. Flavor, tenderness and overall acceptability increased of curing treatment. The over all acceptability increased for the Iraqi method (T3) incomparisom with typical method and the control. There were a decrease ( p < 0.05) in sensory score when the period storage increased. This study revealed no significant differences between the Iraqi method curing and the typical method, Thus we can recommend using the Iraqi method of curing on large scale basis.